2019
DOI: 10.1016/j.ygyno.2019.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Long term resource consequences of a nationwide introduction of robotic surgery for women with early stage endometrial cancer

Abstract: Long term resource consequences of a nationwide introduction of robotic surgery for women with early stage endometrial cancer Malene Korsholm, MScPH ad

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
1
9
0
1
Order By: Relevance
“…By using an ERAS programme with standardised discharge criteria and by treating both groups similarly we were able to demonstrate the actual short and similar length of hospital stay in both groups from time of arrival in the operating theatre to discharge from the ward. In accordance with our findings, a recently published Danish study investigating the long-term resource consequences of introducing robotic surgery for treatment of early endometrial cancer, could not demonstrate a significant difference in days of hospitalisation when adjusting for time trends (Korsholm, et al 2019). The robotic surgery generated additional costs, and no long term cost savings.…”
Section: Cost-effectiveness and Qalysupporting
confidence: 90%
“…By using an ERAS programme with standardised discharge criteria and by treating both groups similarly we were able to demonstrate the actual short and similar length of hospital stay in both groups from time of arrival in the operating theatre to discharge from the ward. In accordance with our findings, a recently published Danish study investigating the long-term resource consequences of introducing robotic surgery for treatment of early endometrial cancer, could not demonstrate a significant difference in days of hospitalisation when adjusting for time trends (Korsholm, et al 2019). The robotic surgery generated additional costs, and no long term cost savings.…”
Section: Cost-effectiveness and Qalysupporting
confidence: 90%
“…A longer recovery time may impact on patient and employment costs, with greater loss of earnings and longer return to work or contribution to society activities as compared with MIS. Korsholm et al 18 reported no significant difference in return to the labour market or use of sickness benefits in a study from Denmark, however; in their study, robotic surgery was associated with greater cost than both LH and OH, unlike this UK analysis. Allowing for a number of OH cases, the disparity in MIS uptake across England 8 does indicate that there is room for improvement in increasing the proportion of MIS cases thereby benefiting both the patient and the healthcare economy.…”
Section: Discussionmentioning
confidence: 56%
“…In recent population‐based studies we showed that a nationwide Danish adoption of RAS completely transitioned the surgical approach to minimally invasive surgery and was, in general, associated with a reduced risk of severe complications and improved survival; primarily for two‐thirds of the patients who were defined as frail 29,30 . In the present study, more than two‐thirds of the patients underwent RAS at the end of the observation period and this incurred, in general, increased costs 31 . The present study suggests that this is not the case for obese women.…”
Section: Discussionmentioning
confidence: 47%